Human Resources Specialists in the Changing Conditions of Modern Organizations - Alena D. Lyubimova (Управление культурой)
Despite the current professional standard for a personnel management specialist in our country, in practice this area of work is implemented in accordance with the culture adopted in the organization, norms, values, company characteristics (industry, size, organizational structure specifics, etc.). At the same time, a common idea about the profession of a HR specialist is the image of a “HR manager”, which is not relevant in modern realities, since companies are focused on versatile areas of work with employees - recruitment, adaptation, training, development and career growth, involvement, conflict resolution and etc. The article presents the specifics of various HR specializations in personnel management and describes related areas of work that ensure success not only for the employee himself, but for the company as a whole. The Human Resources Specialist is an expert in the administration of HR processes who ensures compliance with labor laws. A recruiter, or recruiter, is a professional whose main task is to provide highly qualified specialists. The timely “delivery” of professionals and specialists depends on the competencies and quality of work of recruiters, it is possible to maintain productivity and efficiency. Staff training and development specialists help companies plan and organize a staff development program. The work of these specialists is diverse: from organizing external training for employees to developing their own training programs, creating training courses to improve the competence of employees. A personnel management specialist, or HR manager, is a specialist who implements a wide range of functions and tasks, ranging from the search and selection of personnel, its adaptation to the formation of motivation systems and personnel reserve programs. Modern changes and the consequences of the pandemic have influenced the development of non-format HR specializations - experts, consultants for various functions and tasks of personnel management outside the organization itself. They can be called HR-freelancers - highly qualified professionals who build their careers individually, develop a personal brand and solve problems to improve the efficiency of HR management.